Preoperative and intraoperative factors that influence development of systemic inflammatory response syndrome following percutaneous nephrolithotomy - Donthiri, Sandeep Reddy; Shaik, Jamal; Praveen, A. P. S. Guru; Ramesh, M. Laxmi; Reddy, P. Vedamurthy (International Journal of Research in Medical Sciences, 2024)
Background: Sepsis is one of the complications of PCNL. Various pre operative and intra operative factors are associated with its development. Sepsis initially starts with SIRS-Systemic Inflammatory Response Syndrome. Early diagnosis and treatment of SIRS also prevents the development of sepsis during the post operative period which markedly reduces the hospital stay and cost of care associated with the treatment and prevents mortality which can be attributed to septic shock. This study aimed to study the incidence of SIRS in the patients who underwent PCNL. Also, to study the pre operative and intra operative factors associated with development of SIRS in patients who underwent PCNL. Methods: An observational study was conducted in the Department of Urology, Narayana Medical College and Hospitals, Nellore for 18 months from June 2021 to November 2022. A convenient sample of 100 were selected among the patients who underwent percutaneous nephrolithotomy procedure. Results: 36% developed SIRS during the course of treatment. The association between development of SIRS and pelvic urine culture and sensitivity (P=0.018), stone culture and sensitivity (P=0.0004), requirement of blood transfusion (P=0.03) and operating time (P=0.0001) was statistically significant. Conclusions: The patients with risk factors like positive pelvic urine culture and sensitivity, positive stone culture and sensitivity, requirement of blood transfusion and longer duration of surgery are to be carefully monitored and treated to prevent the development of SIRS.